2019
DOI: 10.1093/aje/kwz092
|View full text |Cite
|
Sign up to set email alerts
|

Associations of Maternal Cell-Phone Use During Pregnancy With Pregnancy Duration and Fetal Growth in 4 Birth Cohorts

Abstract: Results from studies evaluating potential effects of prenatal exposure to radio-frequency electromagnetic fields from cell phones on birth outcomes have been inconsistent. Using data on 55,507 pregnant women and their children from Denmark (1996–2002), the Netherlands (2003–2004), Spain (2003–2008), and South Korea (2006–2011), we explored whether maternal cell-phone use was associated with pregnancy duration and fetal growth. On the basis of self-reported number of cell-phone calls per day, exposure was group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 53 publications
0
16
0
1
Order By: Relevance
“…In this case, the possibility of direct effects must be considered, as some published data suggest an increased susceptibility of the fetus to thermal effects related to HF-EMF [33], while no specific adverse outcomes seem associated with SMF and ELF-EMF exposure [8][9][10][11]20]. Recently, some quite large epidemiological studies on cohorts of pregnant women with ELF-MF exposure [34,35] and with exposure to higher EMF frequencies from other sources [36,37] have been published; no associations with adverse maternal outcomes were found for ELF-MF, while possible associations with outcomes as preterm births were reported for higher frequencies, and the results deserve further confirmation in future studies.…”
Section: Workers At Particular Risk For Electromagnetic Fields Exposurementioning
confidence: 99%
“…In this case, the possibility of direct effects must be considered, as some published data suggest an increased susceptibility of the fetus to thermal effects related to HF-EMF [33], while no specific adverse outcomes seem associated with SMF and ELF-EMF exposure [8][9][10][11]20]. Recently, some quite large epidemiological studies on cohorts of pregnant women with ELF-MF exposure [34,35] and with exposure to higher EMF frequencies from other sources [36,37] have been published; no associations with adverse maternal outcomes were found for ELF-MF, while possible associations with outcomes as preterm births were reported for higher frequencies, and the results deserve further confirmation in future studies.…”
Section: Workers At Particular Risk For Electromagnetic Fields Exposurementioning
confidence: 99%
“…These findings indicate the considerable contribution of medical teams, particularly obstetrics, in providing accurate information to pregnant women. Studies indicate that although the issue has not been definitely proven, and cell phone use during pregnancy may be associated with a small impact on birth outcomes, the accumulative impact on public health may be considerable (23).…”
Section: Discussionmentioning
confidence: 99%
“…They also reported that prenatal and early postnatal exposure to cell phone radiation were associated with behavioral disorders such as hyperactivity (15). Huss et al planned a meta-analysis and found that the use of cell phones during pregnancy was significantly associated with preterm labor and a shorter duration of pregnancy (23). In a population-based birth cohort study on 2618 children, Guexens et al (12) concluded that teacher-reported behavioral disorders at the age of seven were associated with cell phone use during pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, a possible association between exposure to extremely lowfrequency EMFs and childhood leukemia [Ahlbom et al, 2000;Kheifets and Shimkhada, 2005;Kabuto et al, 2006] and a possible relationship between mobile phone use (radiofrequency EMFs) and brain tumors [Interphone Study Group, 2010;Hardell et al, 2011;Yang et al, 2017] have been extensively investigated. Epidemiological studies on the relationship between exposure to extremely low-frequency and radiofrequency EMFs during pregnancy and birth outcomes, however, are limited, and the results are inconsistent [Bracken et al, 1995;de Vocht et al, 2014;Tsarna et al, 2019]. Studies on the health effects of intermediate-frequency (IF) EMFs, meanwhile, are rare.…”
Section: Introductionmentioning
confidence: 99%